Health Promotion (IntechOpen, 2026)
This book aims to highlight various effective strategies for promoting and disseminating the concept of wellness. Through the work of numerous authors, the book will range from organizational issues to new studies highlighting how to adopt healthy lifestyles. The last chapter, on the other hand, serves as a closing chapter, in which the authors describe the various mechanisms by which constant and continuous physical activity is crucial in reducing risk factors, specifically the increase of antioxidant systems. The increase in antioxidant defenses related to physical activity represents a vital component in understanding and modulating anti-ageing.